Loading...

-5=6n+7 -5-7=6n+7-7 -12=6n -12/6=6n/6 -2=n

6n = 12 n = 2

6n/10=3 6n=30 n=5

6n + 17 = 5 subtract 17 from both sides 6n = -12 divide both sides by 6 n = -2 (negative 2)

Suppose n is the smaller integer. Then the larger integer is n + 1, so that 5 times the larger is 5*(n + 1). Their sum is n + 5*(n + 1) = 6n + 5 Therefore 6n + 5 = 41 6n = 41 - 5 = 36 So that n = 36/6 = 6

The variable is n and n=-5/6 Hope this helps :)

I need to solve this problem using the multiplication principle. -5/6n=-10 solution: -5/6n=-10 (- gets canceled) 5/6n=10 ½=6n N=1/6*2 N=1/12

6n = 42 n = 42/6 n = 7

If you mean -5(6n+6) = 30 then -30n -30 = 30 and so n = -2 when evaluated

All non-prime numbers are divisible by prime numbers. Now the smallest to prime numbers are 2 and 3. The next prime number is 5, which is 6*1 - 1. All larger numbers are in the form of one of 6n, 6n+1, 6n+2, 6n+3, 6n+4, 6n+5. Now 6n is divisible by 2 and so cannot be a prime. 6n+2 and 6n+4 are also divisible by 2 and so cannot be prime. 6n+3 is divisible by 3 and so cannot be prime. That leave 6n+1 and 6n+5 as the only two forms than can be prime. Note though that 6n+5 = 6m-1 where m = n+1. So all primes are of the form 2, 3, 6n+1 and 6n-1. And all primes can be divided by primes. The result follows.

If: -6n-2n = 16 Then: n = -2

6n - 2n + 2 = n - 11 4n - n = -11 - 2 3n = -13 n = -13/3 = -4.3333

If 6n = 1 then n = 1/6.

7n + 1 = 6n + 8 7n=6n+7 (minus 1 from each side) n=7 (7n-6n equals n, you are left with n=7)

Let the second of the three consecutive multiples of 6 be 6n Then the first is 6n - 6 and the last is 6n + 6; and: (6n - 6) + 6n + (6n + 6) = 666 → 18n = 666 → n = 37 → the consecutive multiples of 6 which sum to 666 are 216, 222, 228

T(n) = 25 - 6n

7n3 + 6n = n*(7n2 + 6)

You replace "n" with its value; then you do the multiplication (6n means 6 times n).

6n - 4; let n = 1, 2, 3, 4, 5,... If n= 1, 6n - 4 = 6(1) - 4 = 2 If n = 2, 6(2) - 4 = 8, so the common difference is 6. Thus, the first 5 terms are 2, 8, 14, 20, 26, and 32.

If you mean -5(6n+6) = 3 then -30n -30 = 3 and so -30n = 33 meaning that the value of n = -1.1

-6n-2n 16 can be solved mathematically getting n = - 2.

If you mean: -6n-2n = 16 then -8n = 16 and the solution to the equation is n = -2

n = 1 7n + 6n - 5 = 4n + 4 13n - 5 = 4n + 4 13n - 4n - 5 = 4n - 4n + 4 9n - 5 = 4 9n -5 + 5 = 4 + 5 9n = 9 n = 1

I'm not sure about the 37 thing but here is from NIOSH method in how to prepare 6N HCL -pipette 25.64 mL of 11.7 N (37% HCL fuming) to 50 mL volumetric flask and top up with distilled water GOOD LUCK Always add acid to water.

6n - 11 = 49 Add 11 to both sides: 6n = 60 Divide both sides by 6: n = 10